SEGMENTATION AND INTERACTION OF NORMAL FAULTS IN CENTRAL GREECE - Kokkalas, S. (Bulletin of the Geological Society of Greece, 2010)
The aim of this study is to improve our understanding on the mechanical interaction and linkage process between normal fault segments. Faults grow by the process of radial propagation and the linkage of segments, as strain increases, evolving to large fault systems. For this purpose we conducted a combined field and photogeological study on two major segmented fault zones in Central Greece, the Atalanti and Arkitsa fault zones. This approach includes effects of fault size and spatial distribution, scaling laws and footwall-hanginwall topography. Throw distribution and the geometry of the segmented fault arrays were analyzed in order to investigate the complexity of fault zones, the fault linkage process and the geometric characteristics of the relay zones formed between individual segments. The correlation of fault throw with fault length (D-L) and the ratios of overlap-separation (OL-S), separation-fault segment length (S-L) and relay displacement vs. separation (Dr-S) were examined in order to give an insight for fault segment interaction and linkage .